2013
DOI: 10.1108/08858621311302877
|View full text |Cite
|
Sign up to set email alerts
|

Customer flow: evaluating the long‐term impact of marketing on value creation

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Competitive advantage will add value to the company in order to sustain competition in the market. The advantage of competitive advantage is surely for company performance (Rizwan et al, 2014) and it is assessed mainly from customer perspective (Tretyak & Sloev, 2013). In addition, many companies in various countries have started to focus on marketing strategies of the environmental friendly product (Hartmann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Competitive advantage will add value to the company in order to sustain competition in the market. The advantage of competitive advantage is surely for company performance (Rizwan et al, 2014) and it is assessed mainly from customer perspective (Tretyak & Sloev, 2013). In addition, many companies in various countries have started to focus on marketing strategies of the environmental friendly product (Hartmann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it will be able to influence green awareness among consumer, hence improves consumer purchasing intention for environmentally friendly product (Mourad et al, 2012). Besides, through advertisement, some attributes from the environmentally friendly product can be demonstrated (Tretyak & Sloev, 2013), hence improve consumer care towards environmental friendly product and consumer purchase intention (Wu & Chen, 2014). It has appeared that consumer interest in the environmentally friendly product in Indonesia is still low compared to the conventional product (Suki, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to effectively create and deliver value to the customers as well as to capture profits from these activities impacts financial performance of the company and its sustainability. It is demonstrated that marketing has a positive long-term impact on value creation (Tretyak and Sloev, 2013). The notion of value and various activities related to value are also most frequently mentioned in BM definitions (Amit and Zott, 2001;Chesbrough and Rosenbloom, 2002;Magretta, 2002;Teece, 2010).…”
Section: Analyzing Marketing Concepts As a Core Stone Of Business Model Researchmentioning
confidence: 99%
“…Participative research is being successfully deployed in consumer research, with Tsybina and Rebiazina (2013) analysing the impact of customer-interconnectedness on portfolio management, and Tretyak and Sloev (2013) refining a model of customer flow to examine the long-term impact of marketing activities on value creation. However, it is yet to gain traction in tourism, in spite of implicit demand for it.…”
Section: Participative Inquirymentioning
confidence: 99%